Manajemen Risiko Pembiayaan Murabahah di BPR Syariah Amanah Ummah Cabang Bogor - Ulhaq, Alvin Aulia; Nawawi, Kholil; Muhlisin, Sofian (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the Murabahah mechanism as well as the practices and risk management mechanisms for Murabahah financing at the Sharia People's Financing Bank or BPRS Amanah Ummah Bogor Branch Office. The research method used is a descriptive method in the form of words, images and not numbers due to the application of qualitative methods. Apart from that, everything that is collected may be the key to what has been researched. The results of the research show that 1) Murabahah financing carried out by BPRS Amanah Ummah, especially the Bogor Branch office, is financing aimed at financing both assets, capital and building materials based on criteria and specifications that are completely handed over to the customer. So the Murabahah mechanism is to submit first, after that the BPRS will analyze the needs, survey, and also 5C + 1S analysis, after everything has been analyzed then the next stage is the contract. 2) In the murabahah financing risk management process, this process has 3 stages, namely identification, measurement and risk control. Keywords: Management; Risk; Financing; Murabahah